(untitled) (Global Journal of Human-Social Science, 2024)
Research from the fields of second language education and genre pedagogy indicates that students, including those from culturally diverse backgrounds, will improve their achievement if they engage with the meaning-making conventions of disciplinary texts. However, there is no current study on the nature of teaching practices for supporting such work in Hong Kong. The purpose of this study is to investigate how frontline teachers can use Genre pedagogy with an interdisciplinary teaching model to enhance culturally diverse students’ motivation to learn Chinese History and deepen their understanding of history concepts. The research team worked with the teachers to design the teaching materials and learning activities in a Hong Kong secondary school. Then, they investigated the students’ perception of the pedagogy by questionnaire, conducted interviews with the teacher, and evaluated and reflected on the whole design of Genre pedagogy in Chinese History classrooms. 80 NCS secondary school students (N = 80), with an average age of 14, participated in this study.